Spaces of aid : how cars, compounds and hotels shape humanitarianism - Smirl, Lisa, 1975-2013 (Zed Books, 2015)
A landmark work that - through analysing the three key symbolic sites of the grand hotel, the SUV and the compound - shows why we urgently need to think differently about humanitarian theory and practice.